Voxel-Based Statistical Analysis of 3D Immunostained Tissue Imaging - Vandenberghe, Michel E.; Souedet, Nicolas; Hérard, Anne-Sophie; Ayral, Anne-Marie; Letronne, Florent; Balbastre, Yaël; Sadouni, Elmahdi; Hantraye, Philippe; Dhenain, Marc; Frouin, Frédérique; Lambert, Jean-Charles; Delzescaux, Thierry (Frontiers in Neuroscience, 2018)
Recently developed techniques to visualize immunostained tissues in 3D and in large samples have expanded the scope of microscopic investigations at the level of the whole brain. Here, we propose to adapt voxel-based statistical analysis to 3D high-resolution images of the immunostained rodent brain. The proposed approach was first validated with a simulation dataset with known cluster locations. Then, it was applied to characterize the effect of ADAM30, a gene involved in the metabolism of the amyloid precursor protein, in a mouse model of Alzheimer's disease. This work introduces voxel-based analysis of 3D immunostained microscopic brain images and, therefore, opens the door to localized whole-brain exploratory investigation of pathological markers and cellular alterations.